The comparison of new and classical point mutations associated with clarithromycin resistance in Helicobacter pylori strains isolated from dyspeptic patients and their effects on phenotypic clarithromycin resistance - Kocazeybek, B. S.; Sarp, T. Ziver; Ozbey, D.; Gareayaghi, N. (Wiley, 2019)
[Abstract Not Available]
32nd International Workshop on Helicobacter and Microbiota in Inflammation and Cancer (EHMSG) -- SEP 05-07, 2019 -- Innsbruck, AUSTRIA